Strain rate effect on the failure strain and hardness of metallic armour plates subjected to high velocity projectile impact - Shah, Qasim H. (School of Engineering, Taylor’s University College, 2006)
Post impact strain measurements of damaged plates were carried out experimentally after launching a spherical steel projectile at varying velocities against a fixed thin plate targets made of copper and steel materials and constrained at their outer periphery. Penetration or partial perforation of the target plates was achieved for projectile velocities of 120 m/s. The strain rates achieved during the experiments varied from 8000s-1 to 15000 s-1 for steel specimens and from 9000 s-1 to 19000 s-1 for copper specimens for the projectile speeds of 68 to 120 m/s. Strain measurements for static and dynamic loading showed that steel deformation is excessive before failure resulting in higher failure strain at high strain rates while the failure strain for copper at high loading rates causes separation of material before reaching very large strains. At the same loading rates the plate thinning of steel was recorded to be severe than copper. Hardness values of materials subjected to high strain rate were measured experimentally showing a strong dependency upon strain rates calculated by using LS-DYNA software. Strain rate effect on the failure strain of metals was investigated.